98 Lack of Consensus on Anti-thrombotic Therapy in Patients Undergoing Tavi – an Online Survey from Uk Tavi Operators. (31st May 2014) - Hashmi, Izhar; Wiper, Andrew; More, Ranjit; Sogliani, Franco; Tang, Augustine; Roberts, David
Abstract : Introduction: The incidence of cerebrovascular ischaemic events during and early after Trans-catheter Aortic Valve Implantation (TAVI) procedure remains a major concern. Peri-procedural events may be due to embolization of calcified material or atheromatous debris from aorta. Post-TAVI events may be attributed to thrombogenicity of bioprosthesis, fissured/denuded native valve and new onset atrial fibrillation. Anti-coagulation with unfractionated heparin during and dual anti-platelet therapy (DAPT) after TAVI is generally recommended but evidence for this approach is lacking. Further, there is no specific guidance on post-TAVI anti-thrombotic strategy in patients with atrial fibrillation and the duration of DAPT. Methods: An online survey to find out real life practice of anti-thrombotic therapy before, during and after the TAVI procedure was conducted. Results: Seventeen TAVI operators participated in the survey. All operators administer heparin during the procedure but only 71% measure ACT, with target ACT varying from >200 to >300 seconds. Pre-TAVI, 29% of operators give DAPT, 47% give single anti-platelet therapy (SAPT), 18% do not give anti-platelet therapy and one TAVI operator has no preference. Post-TAVI, 71% operators prescribe DAPT and 29% give SAPT. Out of those who prescribe DAPT post-TAVI, 8% give it for one month, 67% for 3 months, 8% for 6 months and 17% did not specify the duration. Only one TAVI operator tests for clopidogrel resistance and substitutes it with ticagrelor in non-responders. In patients with atrial fibrillation 35% operators prescribe post-TAVI Warfarin only, 47% combine it with SAPT and 18% did not specify whether they give any anti-platelet in addition to Warfarin. 94% start Warfarin during hospital stay following TAVI but one operator starts it 3 months later (when DAPT ceases). Conclusion: This survey highlights huge variation in the individual management of anti-thrombotic treatment before, during and after TAVI procedures. This reflects the present lack of evidence on the optimal dose of intra-procedural heparin (target ACT to be achieved) and the value of SAPT versus DAPT (dosing and duration). Early introduction/re-introduction of warfarin in patients with atrial fibrillation is recognised but approach towards anti-platelet therapy in these patients is inconsistent. Randomised trials to determine optimal anti-thrombotic strategies in the high risk TAVI population are clearly required.